Preparation and Characterization of Magnetic Co0.5Mn0.5Fe2O4-Chitosan Nanoparticles as Surfactants in Oilfield - Zheng, X.F.; Lian, Q. (Asian Journal of Chemistry, 2014)
The novel magnetic Co0.5Mn0.5Fe2O4-chitosan nanoparticles has the advantage of excellent biodegradation and a high level of controllability. The Co0.5Mn0.5Fe2O4-chitosan nanoparticles was prepared successfully. The size of the Co0.5Mn0.5Fe2O4-chitosan nanoparticles were all below 100 nm. The saturated magnetization of the Co0.5Mn0.5Fe2O4-chitosan nanoparticles could reach 80 emu/g and showed the characteristics of super-paramagnetism at the same time. The images of TEM and SEM electron microscopy showed that the cubic-shape magnetic Co0.5Mn0.5Fe2O4 particles were encapsulated by the spherical chitosan nanoparticles. The evaluation on the interfacial properties of the product showed that the interfacial tension between crude oil and water could be reduce to ultra-low values as low as 10-3 mN/m when the magnetic Co0.5Mn0.5Fe2O4-chitosan nanoparticle was used in several blocks in Shengli oilfield without other additives. Meanwhile, the magnetic Co0.5Mn0.5Fe2O4-chitosan nanoparticles possessed good salt-resisting capacity.